Synthesis, Characterization, and Antifungal Evaluation of Thiolactomycin Derivatives. (May 2020) - Lv, Pei; Chen, Yiliang; Wang, Dawei; Wu, Xiangwei; Li, Qing X.; Hua, Rimao
Highlights: A series of 3-acylthiotetronic acid derivatives were synthesized. Most target compounds exhibited excellent fungicidal activities. Compound 11c and 11i displayed broad spectrum fungicidal activity. The EC50 of 11c and 11i were 1.9–10.7 and 3.1–7.8 μg/mL against the tested fungi. A statistically significant CoMFA model with high prediction abilities was obtained. Abstract: 5-Substituted benzylidene 3-acylthiotetronic acids are antifungal. A series of 3-acylthiotetronic acid derivatives with varying substitutions at the 5-position were designed, synthesized, and characterized, based on the binding pose of 3-acyl thiolactone with the protein C171Q KasA. Fungicidal activities of these compounds were screened against Valsa Mali, Curvularia lunata, Fusarium graminearum, and Fusarium oxysporum f. sp. lycopersici . Most target compounds exhibited excellent fungicidal activities against target fungi at the concentration of 50 μg·mL −1 . Compounds 11c and 11i displayed the highest activity with a broad spectrum. The median effective concentration (EC50 ) values of 11c and 11i were 1.9–10.7 and 3.1–7.8 μg·mL −1, respectively, against the tested fungi, while the EC50 values of the fungicides azoxystrobin, carbendazim, and fluopyram were respectively 0.30, 4.22, and > 50 μg·mL −1 against V. Mali ; 6.7, 41.7, and 0.18 μg·mL −1 against C. lunata ; 22.4, 0.42, and 0.43 μg·mL −1 against F. graminearum ; and 4.3, 0.12, and > 50 μg·mL −1 against F. oxysporum f. sp. lycopersici . The structures and activities of the target compounds against C. lunata were analyzed to obtain a statistically significant comparative molecular field analysis (CoMFA) model with high prediction abilities ( q 2  = 0.9816, r 2  = 0.8060), and its reliability was verified. The different substituents on the benzylidene at the 5-position had significant effects on the activity, while the introduction of a halogen atom at the benzene ring of benzylidene was able to improve the activity against the tested fungi.